1999
DOI: 10.1142/s0217979299002095
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of Novel Magnetorheological Fluids Having Improved Stability and Redispersibility

Abstract: A novel class of relatively stable and redispersible MR fluids based on meso-scale magnetic particles of iron or nickel zinc ferrite and nano-scale additives is described. For a flux density B ~ 1 Tesla, the iron based MR fluids exhibited yield stresses of ~100 kPa. For ferrite based fluids the yield stress values were as high as ~15 kPa at B ~ 1T. The yield stresses at the flux density required for magnetic saturation increase quadratically with the saturation magnetization of the particulate material, in goo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(49 citation statements)
references
References 6 publications
1
48
0
Order By: Relevance
“…Recently, it was reported that the use of ferrouid (FF) is an effective way to reduce the settling rate of micron-sized particles in MR uid. [15][16][17][18][19] On the application of a magnetic eld, the micron-sized particles become polarized and gather in chains or clusters due to dipole-dipole interaction. It is seen that formation of these clusters creates microcavities within the structures.…”
Section: -4mentioning
confidence: 99%
“…Recently, it was reported that the use of ferrouid (FF) is an effective way to reduce the settling rate of micron-sized particles in MR uid. [15][16][17][18][19] On the application of a magnetic eld, the micron-sized particles become polarized and gather in chains or clusters due to dipole-dipole interaction. It is seen that formation of these clusters creates microcavities within the structures.…”
Section: -4mentioning
confidence: 99%
“…In order to reduce particle aggregation and settling, different procedures have been proposed: (1) adding thixotropic agents (ex. Carbon fibers, silica nanoparticles) (Bossis, Volkova et al 2003;De Vicente, López-López et al 2003); adding surfactants(ex Oleic or stearic acid) (Phulé and Ginder 1999); (3) adding magnetic nanoparticles López-López, de Vicente et al 2005); (4) the use of viscoplastic media as a continuous phase (Rankin, Horvath et al 1999) and (5) water-in-oil emulsions as carrier liquids . Glycerol and surfactants are used in water based fluid as stabilizers.…”
Section: Magnetorheological Fluidmentioning
confidence: 99%
“…(10)(11)(12) and T 2 is the transverse relaxation time associated with the dephasing of different spins. T 2 is generally shorter than T 1 .…”
Section: Ideal Monodomain Particles Made From Ferromagnetic Materialsmentioning
confidence: 99%
“…There has been a recent spate of interest in the use of metallic Fe nanoparticles for environmental remediation of subsurface chlorinated hydrocarbons, [8][9][10][11] but here the Fe (0) chemistry is central, rather than the magnetism. Micrometer-scale particles are used in magnetorheological fluids, [12] whose viscosities change by orders of magnitude when a magnetic field is applied. Although nanoparticles may be mixed in as well, [13] the magnetism of these materials is dominated by the multidomain structure.…”
mentioning
confidence: 99%